Issue mapping for an ageing Europe - Rogers, Richard 1965-; Sánchez-Querubin, Natalia; Kil, Aleksandra (Amsterdam Univ. Press, 2015)
This book offers a practical and theoretical examination of issue mapping with digital methodologies. The issue at stake concerns the European population where in the near future the old will outnumber the young, threatening the stability of both pension and healthcare systems, and changing the migration patterns of those who need and who provide care. Drawing on the latest theoretical approaches to issue mapping, the authors put them into practice through online mapping techniques to demonstrate ways of exploring the complex issue of demographics and the debates surrounding data available online. The authors use the websites of non-governmental organizations to locate the ageing issue agenda, and varying levels of attention given to the shared as well as isolated concerns. Online job portals provide data about not only employment opportunities but also the movement of care workers, pointing up potential 'victim states' in the ageing world. Search engine queries are designed to identify cultural philosophies about ageing, not to mention European anti-ageing cuisine